2021
DOI: 10.1016/j.jor.2020.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and clinical analysis of the use of asymmetric vs symmetric polyethylene inserts in a mobile bearing total knee arthroplasty

Abstract: This study compared the effects of symmetric and asymmetric designs for mobile bearing polyethylene insert for total knee arthroplasty (TKA), both clinically and biomechanically through experimental cadaver tests. Methods: 303 patients implanted with a mobile bearing TKA were retrospectively analyzed up to 2-year follow-up with relative scores. The same femoral and tibial components were used for all the patients; 151 patients received a Symmetric Design (SD) insert and 152 an Asymmetric Design (AD). A biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Under the condition of the same tibial and femoral components, symmetric and asymmetric polyethylene inserts were used in 151 and 152 patients, respectively. During standing and squatting, the contact stress in the tibial component was lower in those with asymmetric inserts (Figure 1B), at the 2-year follow-up, the asymmetric polyethylene insert group was able to perform certain routine movements better and without any pain, while patients in the symmetrically designed polyethylene group reported pain, validating the FEA results (Castellarin et al, 2021).…”
Section: Refencesupporting
confidence: 66%
“…Under the condition of the same tibial and femoral components, symmetric and asymmetric polyethylene inserts were used in 151 and 152 patients, respectively. During standing and squatting, the contact stress in the tibial component was lower in those with asymmetric inserts (Figure 1B), at the 2-year follow-up, the asymmetric polyethylene insert group was able to perform certain routine movements better and without any pain, while patients in the symmetrically designed polyethylene group reported pain, validating the FEA results (Castellarin et al, 2021).…”
Section: Refencesupporting
confidence: 66%
“…The polyethylene inlay of FB implants is secured on the tibial plateau. On the other hand, MB implants allow rotation of the polyethylene inlay around its longitudinal axis, miming the physiological kinematics of the knee and promoting a wider range of motion [ 22 , 34 , 93 ]. Previous evidence suggested that MB may promote greater outcomes in functional scores and complications [ 40 , 44 , 45 , 75 , 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Department of Orthopaedic Surgery, Niigata Medical Center, Niigata, Japan. 3 Department of Health and Sports, Faculty of Health Sciences, Niigata University of Health and Welfare, Niigata, Japan.…”
Section: Abbreviationsmentioning
confidence: 99%
“…In recent years, TKA, which has both a medial pivot mechanism with high medial constraint and a mobile mechanism of insert, has been developed and clinically used. However, previous studies have only described kinematics of up to less than 90° of the knee joint [3, 4] and the dynamic kinematics of this mobile medial pivot‐type TKA (MMPTKA) in the deep flexion phase remains unclear. Whether MMPTKA, which employs both MBTKA and MPTKA mechanisms, can demonstrate both advantages at the same time also remains unclear.…”
Section: Introductionmentioning
confidence: 99%